1996
DOI: 10.1073/pnas.93.9.3859
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a major gene for resistance to fusiform rust disease in loblolly pine by genomic mapping.

Abstract: Genomic mapping has been used to identify a region of the host genome that determines resistance to fusiform rust disease in loblolly pine where no discrete, simply inherited resistance factors had been previously found by conventional genetic analysis over four decades. A resistance locus, behaving as a single dominant gene, was mapped by association with genetic markers, even though the disease phenotype deviated from the expected Mendelian ratio. The complexity of forest pathosystems and the limitations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
108
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(114 citation statements)
references
References 22 publications
(20 reference statements)
2
108
0
1
Order By: Relevance
“…in poplar ( Hsiang & Van Der Kamp, 1985;Cervera et al ., 1996;Lefevre et al ., 1998). Molecular markers have been identified that are tightly linked to several disease-resistance loci ( Devey et al ., 1995;Wilcox et al ., 1996;Lefevre et al ., 1998;Stirling et al ., 2001), but resistance genes have yet to be cloned and functionally characterized for a forest tree.…”
Section: Introductionmentioning
confidence: 99%
“…in poplar ( Hsiang & Van Der Kamp, 1985;Cervera et al ., 1996;Lefevre et al ., 1998). Molecular markers have been identified that are tightly linked to several disease-resistance loci ( Devey et al ., 1995;Wilcox et al ., 1996;Lefevre et al ., 1998;Stirling et al ., 2001), but resistance genes have yet to be cloned and functionally characterized for a forest tree.…”
Section: Introductionmentioning
confidence: 99%
“…Wilcox et al [19] previously identified and verified the existence of this pathotype-specific resistance gene via genetic mapping. Genetic mapping information for all the currently identified Fr genes is discussed in Section 3.2.…”
Section: Fr Gene Identificationmentioning
confidence: 99%
“…The families were either progeny from selections that are property of privately-owned industrial tree improvement programs, or progeny from selections from public (USDA Forest Service and Georgia Forestry Commission) tree improvement programs. Private industry-owned selections have been assigned a generic single-letter code (except for selection 10-5, which was previously used to map Fr1 [19]) to keep their identity anonymous. Publicly-owned materials are identified by their original tree improvement code.…”
Section: Pine Familiesmentioning
confidence: 99%
See 2 more Smart Citations